(untitled) (Global Journal of Management and Business Research, 2018)
We estimated the socio-economic and fiscal impacts of Short Term Rentals (STRs) on the City and County of Honolulu. The study was commissioned by the Hawaii Vacation Rental Owners Association (HVROA) on the island of Oahu in 2012. The study was aimed at informing the debate on the Planning Commission’s draft bill and underlining the economic consequences of the Department of Planning and Permitting’s announced intent to strengthen existing law and shut down STRs without permits in the near future. Our study showed significant economic benefits to the populace of Oahu. These included contributions to economic output between 752.3 million and 1.10 billion, contributions to earnings between 240.6 million and 339.2 million along with the generation of 7,566 to 9,993 jobs in the County. Several articles appearing in October 2017 both in the Honolulu Star Advertiser and the Honolulu Travel Forum show that Oahu is still looking at Short Term Rental regulation changes. Thus the issue which is an ongoing concern could benefit from the policy discussion in the paper.